2014
DOI: 10.1111/jopy.12142
|View full text |Cite
|
Sign up to set email alerts
|

Value Stability and Change in an ISAF Contingent

Abstract: Studying an International Security Assistance Force contingent on tour in Afghanistan, the aim of the present study was to test assertions of the relative stability of personal values in a challenging environment. Three hundred twenty Swedish soldiers answered questionnaires on their values before and after a 6-month tour of Afghanistan. Value change and stability were studied via mean-level change, rank-order stability, and individual-level change methods. Regression analysis was used to study the impact of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 46 publications
1
20
0
2
Order By: Relevance
“…Adapting to such events often requires reorganizing one's value priorities (Bardi & Goodwin, ; Bardi et al, ). Systematic attempts to link life events to change in value hierarchies, however, are lacking (see Sundberg, , for an exception). This is an important topic for future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adapting to such events often requires reorganizing one's value priorities (Bardi & Goodwin, ; Bardi et al, ). Systematic attempts to link life events to change in value hierarchies, however, are lacking (see Sundberg, , for an exception). This is an important topic for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research on values commonly analyzed mean‐level change and rank‐order stability (e.g., Bardi et al, ; Cieciuch et al, ; Hofmann‐Towfigh, ; Milfont et al, ; Schwartz, ; Vecchione, Caprara, Dentale, & Schwartz, ). The profile stability of values, however, has rarely been studied (Sundberg, ; Vecchione, Schwartz, et al, ), and never in samples of children. Yet, as Vecchione, Schwartz, et al () argue, changes within the value hierarchy/profile of individuals may have significant implications.…”
Section: Introductionmentioning
confidence: 99%
“…In line with our findings, a recent Swedish study reported that personal values also remained relatively stable after participating in a six-month military deployment to Afghanistan. 46 In contrast, previous studies have shown that experiencing serious adverse life events is associated with increases in neuroticism and decreases in agreeableness and openness. 26,27,47 They suggest that these changes were not rooted in preexposure personality but emerged as a result of exposure to trauma.…”
Section: Discussionmentioning
confidence: 92%
“…Though there is a need to change one’s values as a function of life-changing events (e.g., Vecchione et al, 2016), research has demonstrated that value preferences are comparably stable over time (Bardi et al, 2014). And to the extent that value change occurs, it tends to change slowly and not in any radical fashion (Sundberg, 2016; Vecchione et al, 2020). Though the transition away from communism to democracy may have called for an adaptation of some values; notably, Inglehart and Welzel (2010) argued that the transition to democracy was motivated more by a desire for social freedom than anything else.…”
Section: Structural Change Versus Cultural Socializationmentioning
confidence: 99%